Characterization of a Novel Glutamine Synthetase From Trichinella spiralis and Its Participation in Larval Acid Resistance, Molting, and Development - Zhuo, Tong Xu; Wang, Zhen; Song, Yan Yan; Yan, Shu Wei; Liu, Ruo Dan; Zhang, Xi; Wang, Zhong Quan; Cui, Jing (Frontiers in Cell and Developmental Biology, 2021)
Trichinella spiralis is a major foodborne parasite worldwide. After the encapsulated muscle larvae (ML) in meat are ingested, the ML are liberated in host’s stomach and activated into intestinal infectious larvae (IIL), which develop into adult worm after molting four times. A novel glutamine synthetase (TsGS) was identified from T. spiralis IIL at 10 h post infection, but its biological role in T. spiralis lifecycle is not clear. The aim of this study was to investigate the biological characteristics of TsGS and its functions in larval acid-resistance, molting and development. TsGS has a GS catalytic domain. Complete TsGS sequence was cloned and expressed in Escherichia coli BL21. rTsGS has good immunogenicity. qPCR and Western blotting showed that TsGS was highly expressed at IIL stage, immunofluorescence revealed that TsGS was principally localized at cuticle and intrauterine embryos of this nematode. rTsGS has enzymatic activity of natural GS to hydrolyze the substrate (Glu, ATP and NH4+). Silencing of TsGS gene significantly reduced the IIL survival at pH 2.5, decreased the IIL burden, and impeded larval molting and development. The results demonstrated that TsGS participates in T. spiralis larval acid-resistance, molting and development, and it might be a candidate vaccine target against Trichinella molting and development.